Antiandrogenic Activity of Artemisia herba-alba in Male Albino Rats, with Emphasis on Biochemical Parameters - H. KHATAIBEH, MOAYAD; DARADKA, HAYTHAM (Asian Journal of Chemistry, 2010)
The aqueous extracts of Artemisia herba alba. solution was fed orally to male albino rats at a dose of 100 mg/kg body weight for 60 d. A total of 20 rats were involved in this study and were divided into two groups. Group (A) a vehicle-treated control and group (B) a treated group with Artemisia herba-alba. The dose induces a significant decrease in the weight of reproductive organs (p < 0.01) when compared to controls. The sperm motility and density in cauda epidydimides and testicular ducts were significantly decerased (p < 0.01). A significant decreased (p < 0.001) in spermato-gensis activity is observed in somniferous tubule. Our results demonstrated that administration of Artemisia herba-alba in a dose of 100 mg/kg of body weight for 60 d induces a very significant decrease in glucose level. A significant (p ≤ 0.01) increase in total serum cholesterol level, triglycerides, phospholipids, serum aspartate aminotransferase (AST) and serum alanine aminotransferase (ALT). Treated rats testicular cell population showed a decrease in number of spermatocytes and spermatids (p < 0.001) when compared to controls. Serum hormonal assay indicated a decrease in testoterone and follicular stimulating hormone (FSH) levels in treated rats. A decreased in number female rats impregnated by males receiving treatment was observed and demonstrated by a decrease in the implantation sites and viable fetuses number (p < 0.01).